2002
DOI: 10.1301/00296640260385793
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trace Components of Dietary Fat on Cholesterol Metabolism: Phytosterols, Oxysterols, and Squalene

Abstract: The effect of dietary fats on serum cholesterol is widely assumed to be due solely to the fatty acids and cholesterol they contain. Phytosterols, sterol oxidation products, and sterol precursors such as squalene, however, are often present in dietary fats. Little is known of the physiology of these substances in natural foods and most published diet studies do not consider them at all. Supplementation of the diet with high-dose phytosterols is now recommended for prevention of heart disease, but both recent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 63 publications
1
32
0
2
Order By: Relevance
“…Atherosclerotic lesions not only contain cholesterol, but also a series of oxysterols (Ostlund et al, 2002). In the widely accepted model for the pathogenesis of atherosclerosis, the impact of oxidatively modified low-density lipoprotein (LDL) particles is very important (Brown & Jessup, 1999).…”
Section: Oxysterols and Atherogenesismentioning
confidence: 99%
“…Atherosclerotic lesions not only contain cholesterol, but also a series of oxysterols (Ostlund et al, 2002). In the widely accepted model for the pathogenesis of atherosclerosis, the impact of oxidatively modified low-density lipoprotein (LDL) particles is very important (Brown & Jessup, 1999).…”
Section: Oxysterols and Atherogenesismentioning
confidence: 99%
“…It is known that minor components of the diet, such as plant sterols or phenolic compounds, can affect consumer health (Parr & Bolwell, 2000;Piironen et al, 2000;Ostlund et al, 2002), and thus we also aimed to identify an unknown substance found in the neutral lipid (NL) fraction of reindeer meat during fatty acid analyses (Sampels, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous laboratory studies focused on their potential to reduce cholesterol absorption by the small intestine, [1][2][3][4] and cholesterol uptake by LDL. [5][6][7] In addition, it was reported that phytosterols prevent coronary heart disease, 8 and cardiovascular risks. [9][10][11] However, their potential to reduce the risk of cancer remains controversial.…”
Section: Introductionmentioning
confidence: 99%